Sites of European Antisemitism in the Age of Mass Politics, 1880-1918 - Unowsky, Daniel L., 1966-; Nemes, Robert (Book collections on Project MUSE., 2014)
Explores local incidents of antisemitism and antisemitic violence across Europe in the late nineteenth and early twentieth centuries.